A Risk Management Tool or an Investment Strategy? Understanding the Unstable Farm Insurance Demand via a Gain-Loss Framework. (December 2020) - Cao, Ying (Jessica); Weersink, Alfons; Ferner, Emma
Abstract : Risk management tools are at the core of farm policy in many developed countries, and their effectiveness relies on the appropriate mechanism design. This study developed a gain-loss framework based on prospect theory to examine the reasons for the declining use of the main risk management tool offered to farmers despite growing volatility in returns. Using the administrative Ontario Farm Income Database (OFID) 2003 to 2013 and taking the beef sector as the example, this study found that the gain-loss framework predicts and explains the dynamic program participation pattern better than the conventional expected utility framework. Farms were found to be more likely to stay enrolled in the program when they experienced either larger gains or losses in revenue compared to previous years, suggesting that they were using the insurance programs both as an investment strategy (to seek government subsidies) and as a risk management tool (to protect against business risks), though the effects of revenue losses and hence risk management needs were stronger than gains. In addition, the program payment history and farm characteristics also shape the dynamic participation patterns. The findings increased the understanding of the drivers of withdrawal behavior associated with government-sponsored business risk management programs.